PENGGUNAAN QUIZIZZ SEBAGAI ALAT EVALUASI HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS 5 SDN IV CILEGON - Juni'ah, - (2022)
By seeing the rapid development of technology which is very influential on various aspects, one of which is in the aspect of education, the researchers are interested in conducting Quizizz research as a learning evaluation tool for social studies subjects in class 5C SDN IV Cilegon. The purpose of this research is that it is hoped that Quizizz can be a substitute in the teaching and learning process as an evaluation tool which was originally still done conventionally. One of the benefits of using Quizizz as an evaluation tool is that it makes it easier for teachers to correct and can be an attraction for students with Quizizz being a renewal in the use of learning evaluation tools. Because in Quizizz there are interesting features besides that the researcher also inserts pictures that make students understand more about the questions that the author gives. With Quizizz also indirectly can motivate students in learning. Because students become competitive in the implementation of learning evaluation so that student learning outcomes will increase. This study uses a qualitative approach with classroom action research (CAR) and consists of 2 cycles. In the first cycle of research, students got an average score of 65.74 and the percentage of students' completeness was 48.15%. The second cycle of research increased, namely students got an average score of 79.81 and the percentage of student achievement was 74.1% and had succeeded in achieving the expected results. The results of this study indicate that Quizizz can improve students' social studies learning outcomes.